Pengaruh E-Absensi, Komitmen Organisasi dan Tambahan Penghasilan Pegawai (TPP) Terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervening pada Dinas Pemberdayaan Masyarakat dan Desa Kota Sungai Penuh - Shalsabillah, Ade Rahmadilla; Yulasmi, Yulasmi; Lusiana, Lusiana (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to test the extent of the influence of e-absenteeism, organizational commitment, and employee additional income (TPP) on employee performance with job satisfaction as an intervening variable at the Community Empowerment and Village Office of Sungai Penuh City. The data collection method involved surveys and distributing questionnaires, with a sample of 73 respondents. The analysis method used is structural equation modeling using SmartPLS. The research results show that e-absenteeism has no significant effect on job satisfaction at the Department of Community Empowerment and Villages of Sungai Penuh City. There is a significant effect of organizational commitment on job satisfaction at the Department of Community Empowerment and Villages of Sungai Penuh City. There is a significant effect of employee additional income (TPP) on job satisfaction. There is no significant effect of e-absenteeism on employee performance. There is no significant effect of organizational commitment on employee performance. There is no significant effect of employee additional income (TPP) on employee performance. There is a significant effect of job satisfaction on employee performance. Job satisfaction does not mediate the effect of e-absenteeism on employee performance. Job satisfaction mediates the effect of organizational commitment on employee performance. Job satisfaction mediates the effect of employee additional income (TPP) on employee performance.